2020
DOI: 10.5194/acp-20-10047-2020
|View full text |Cite
|
Sign up to set email alerts
|

Apparent dust size discrepancy in aerosol reanalysis in north African dust after long-range transport

Abstract: Abstract. North African dust reaches the southeastern United States every summer. Size-resolved dust mass measurements taken in Miami, Florida, indicate that more than one-half of the surface dust mass concentrations reside in particles with geometric diameters less than 2.1 µm, while vertical profiles of micropulse lidar depolarization ratios show dust reaching above 4 km during pronounced events. These observations are compared to the representation of dust in the Modern-Era Retrospective analysis for Resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…As the dust impacting Bermuda was transported much farther than sea salt, it is plausible that the characteristic dust peak is at a smaller size than sea salt. This is supported by past studies: (i) African dust reaching Miami, Florida exhibits most of its mass at geometric diameters below 2.1 µm (Kramer et al, 2020); and (ii) mass mean diameters of African dust are less than 1 µm by the time they reach the U.S. East Coast (Perry et al, 1997), which can take approximately a week of transport time (Carlson & Prospero, 1972).…”
Section: Volume Size Distributionssupporting
confidence: 63%
“…As the dust impacting Bermuda was transported much farther than sea salt, it is plausible that the characteristic dust peak is at a smaller size than sea salt. This is supported by past studies: (i) African dust reaching Miami, Florida exhibits most of its mass at geometric diameters below 2.1 µm (Kramer et al, 2020); and (ii) mass mean diameters of African dust are less than 1 µm by the time they reach the U.S. East Coast (Perry et al, 1997), which can take approximately a week of transport time (Carlson & Prospero, 1972).…”
Section: Volume Size Distributionssupporting
confidence: 63%
“…), quartz, feldspar, calcite, and other mineral components (Murray et al, 2012;Scanza et al, 2015;Tang et al, 2016). Clay minerals were widely investigated in ice nucleation studies (Mason, 1960;Eastwood et al, 2008;Pinti et al, 2012;Wex et al, 2014;Kumar et al, 2019a) due to their high abundance in mineral dust composition (Murray et al, 2012), especially after long-range transport (Leinen et al, 1994;Uno et al, 2009). However, recent studies have demonstrated that K-feldspars are the most efficient mineral INP (Atkinson et al, 2013;Zolles et al, 2015b;Whale et al, 2017;Harrison et al, 2019;Yakobi-Hancock et al, 2013;Peckhaus et al, 2016;Kiselev et al, 2017;Augustin-Bauditz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, reference single-mineral dust and surface-collected particles do not fully represent the actual dust transport process in the troposphere due to gravitational dust sedimentation, adsorption of biological materials, and other factors. During dust transport, larger particles settle faster due to gravity, while smaller particles can remain lifted for a longer period, thus possibly playing a different role in cloud formation (Kramer et al, 2020;Maki et al, 2019). Moreover, parameterizations are mainly based on the active mineral components of dust, but the effect of particle size is usually not considered.…”
Section: Introductionmentioning
confidence: 99%
“…It also remains a challenge for climate models to accurately 35 simulate the meteorological processes that play critical roles in dust processes. Yet, these uncertainties tend to amplify as models become more complex (Kok et al, 2017;Ryder et al, 2019;Adebiyi and Kok, 2020;di Biagio et al, 2020;Kramer et al, 2020;Li et al, 2021;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%